2014
DOI: 10.1093/rpd/ncu001
|View full text |Cite
|
Sign up to set email alerts
|

Radiation exposure to nuclear medicine staff involved in PET/CT practice in Serbia

Abstract: The purpose of this work is to evaluate the radiation exposure to nuclear medicine (NM) staff in the two positron emission tomography-computed tomography centres in Serbia and to investigate the possibilities for dose reduction. Dose levels in terms of Hp(10) for whole body and Hp(0.07) for hands of NM staff were assessed using thermoluminescence and electronic personal dosemeters. The assessed doses per procedure in terms of Hp(10) were 4.2-7 and 5-6 μSv, in two centres, respectively, whereas the extremity do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 28 publications
3
5
0
1
Order By: Relevance
“…The average cumulative Hp(10) and Hp(0.07) doses for all staff members were (0.62±0.17) mSv and (0.76±0.21) mSv, respectively. As the cumulative dose is a linear function of time (5,16), we extrapolated the average annual cumulative dose for the PET/CT staff to be (1.06±0.29) mSv for Hp (10) and (1.15±0.32) mSv for Hp(0.07), which is significantly lower than the respective limits of 20 mSv (or the dose constraint of 2 mSv) and 500 mSv (11). 4 provides a comparative analysis of our data to those published in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average cumulative Hp(10) and Hp(0.07) doses for all staff members were (0.62±0.17) mSv and (0.76±0.21) mSv, respectively. As the cumulative dose is a linear function of time (5,16), we extrapolated the average annual cumulative dose for the PET/CT staff to be (1.06±0.29) mSv for Hp (10) and (1.15±0.32) mSv for Hp(0.07), which is significantly lower than the respective limits of 20 mSv (or the dose constraint of 2 mSv) and 500 mSv (11). 4 provides a comparative analysis of our data to those published in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Annual dose limits for the whole body [effective dose, Hp (10)] and extremities [equivalent dose; Hp(0.07)] are 20 mSv and 500 mSv, respectively (4). So far, clinical experience worldwide has demonstrated that these levels are unlikely to be exceeded in the clinical settings based on automated dispensing systems, given the observed trends in NM staff doses over the years (5)(6)(7). On the other hand, Hp(0.07) doses to operating staff working in facilities using semi-automated or manual dispensing systems may be significantly higher and even surpass the annual limits (4, 5,8,9).…”
mentioning
confidence: 99%
“…Wynika z nich, że blisko 80% rejestrowanych dawek skutecznych mieści się w przedziale do 0,1 mSv/kwartał przy dawce granicznej w ciągu 1 roku wynoszącej 20 mSv [6]. Sporadyczne stosowanie manipulatorów podczas czynności wykonywanych z użyciem izotopów promieniotwórczych sprawia, że ręce radiofarmaceutów mogą otrzymywać znaczne dawki promieniowania [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Ręce pracownika bezpośrednio manipulujące źródłem promieniowania, a osłonięte jedynie rękawiczkami (których zadaniem jest wyłącznie ochrona przed skażeniami), mogą być narażone na znaczne dawki promieniowania.…”
Section: Wstępunclassified
“…Assessment of occupational radiation dose in these interventional procedures [1][2][3][4], is based on direct measurement of suitable operational dosimetry quantities (especially in Hp(3) [5][6][7][8][9]) or computational dosimetry methods as MC simulations [10][11][12][13][14]. This is one of the most important topic in radiation protection of personnel at medical application of ionizing radiation, including PET-CT diagnostics [15][16][17][18]. Major source of occupational exposure here is radiation scattered from the patient [4,10,13,14,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%